TURMERIC (Curcuma longa L) EXTRACT EFFECT ON MEMORY FUNCTION - Israwati; Irfannuddin; Eka Febri Zulissetiana; Krisna Murti; Subandrate (Majalah Kedokteran Sriwijaya, 2023)
Memory is the entire process of mental function centered in the brain for raises return knowledge specific about the experience through stages of catch or receive, give code, save, reproduce, and call or bring back. Someone's memory can decrease along increase age. Many factors can influence, among other things: stress, dysfunction pattern-affected acetylcholine life and the environment can cause memory ability to decrease. Stress is a reaction of the body to various situations as threatening as possible and causes a manner physique or physiology that will disturb homeostasis including memorizing. We can consume capable drugs to increase memory and work slows down the descent process of memory. However, using drugs synthetically continuously can raise side effects.1 Using natural material as a trusted drug can reduce effect side effects compared to synthetic drug use.2 A possible treatment alternative is consuming turmeric (Curcuma longa L). Curcumin, the main component biologically active Curcuma longa L, shows various pharmacological activities, including anti-inflammatory, antioxidant, activity immunomodulatory, and neuroprotective. Mechanism enhancement induced memory consequence Turmeric (Curcuma longa L) improves synaptic function by increasing the expression of PSD-95 protein and increasing communication locally between the pyramidal neurons.